IMPLEMENTASI PRINSIP AGILE GOVERNANCE DALAM PENYELENGGARAAN PELAYANAN PUBLIK MELALUI APLIKASI SIAP-MPP DI KOTA PEKANBARU TAHUN 2023 - Shabrina, Nursyah; Rafi, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the implementation of Agile Governance principles in the provision of public services through the SIAP-MPP (Public Service Mall Queue and Complaint Information System) application in Pekanbaru City in 2023. The research method used is descriptive qualitative with data collection through interviews, documentation, and observations of application managers, service officials, and community users. The results of the study indicate that Agile Governance principles such as Systematic and Adaptive Approach, Based on Quick Wins, Human Focused, Simple Design and Continuous Refinement, and Good Enough Governance have been implemented with positive achievements in the form of increased service integration, feature improvements, and user engagement. However, several significant challenges remain such as low levels of community involvement in using the application, technical and infrastructure constraints, low digital literacy, and suboptimal integration between agencies. In general, the SIAP-MPP application is on the path of adaptive digital transformation, but requires further strengthening to make public services more responsive, efficient, and participatory. Keywords: Agile Governance, Public Services, SIAP-MPP Application